Historic preservation for designers - Dedek, Peter B. 1964- (New York : Fairchild Books, 2014)
This book offers a comprehensive overview of historic preservation with a focus on historic interiors, historic building materials, and the adaptive reuse of interiors. This text includes a brief history of preservation in the United States, criteria to determine whether a building is historic, a discussion of preservation law, and how to document historic buildings with a focus on design and understanding functional and aesthetic requirements. The text explores issues including building restoration and rehabilitation standards, adaptive reuse principles,and codes and accessibility requirements. Designers will discover timely information on inspecting historic buildings to determine their age and condition as well as the growing relationship between historic preservation, green design, and the environment.
Includes bibliographical references and index.
Keywords: Historic preservation; Historic buildings -- Conservation and restoration; United States; History